2021
DOI: 10.1001/jamadermatol.2021.2918
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Central Sensitization in Patients With Hidradenitis Suppurativa

Abstract: ain is one of the most prominent and debilitating symptoms of hidradenitis suppurativa (HS) and has been incorporated as a domain in the newly developed core outcome set for HS. 1 The chronic, inflammatory, and painful nature of HS has been postulated to induce a process known as central sensitization (CS). 2 Central sensitization is an increased responsiveness of the pain perception pathway in the central nervous system to normal or subthreshold stimuli, altering and amplifying pain perception. 2 Symptoms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…However, surveybased studies have suggested that central sensitization and neuropathic pain also contribute to the pain experience of patients with HS. 1,5,11,12 Strategies for HS Pain Management…”
Section: Toward Improved Scientific Understanding and Clinical Manage...mentioning
confidence: 99%
“…However, surveybased studies have suggested that central sensitization and neuropathic pain also contribute to the pain experience of patients with HS. 1,5,11,12 Strategies for HS Pain Management…”
Section: Toward Improved Scientific Understanding and Clinical Manage...mentioning
confidence: 99%
“…Pain associated with HS can be categorized into nociceptive, neuropathic, and nociplastic pain, each of which may require distinct treatment strategies 15,24–26 . HS pain has traditionally been considered to be nociceptive.…”
Section: Pathophysiology Of Hs Painmentioning
confidence: 99%
“…Neuropathic 24,25 and nociplastic 26 pain may also play an important role in HS pain. Neuropathic pain arises from sensory nerve dysfunction and often follows a segmental or peripheral distribution pattern as pain radiates along the course of the nerve.…”
Section: Pathophysiology Of Hs Painmentioning
confidence: 99%
“…CS can be present in many conditions with chronic pain, including fibromyalgia, 6 endometriosis, 7 chronic low back pain, 8 , 9 hidradenitis suppurativa, 10 osteoarthritis, 6 , 11 rheumatoid arthritis and chronic migraine. 12 Besides, complex regional pain syndrome (CRPS), also known as Sudeck’s atrophy, is also highly associated with CS and is characterized by significant autonomic and inflammatory features.…”
Section: Introductionmentioning
confidence: 99%